Stabilization of expansive soil using hydrophobic polyurethane foam: A review. (March 2021) - Al-Atroush, M.E.; Sebaey, T.A.
Abstract: Despite the variety of available stabilization methods for the expansive soil, a rapid stabilization and remediation solution for this class of the problematic soil is still needed. Among the available treatment methods, traditional chemical additives such as lime, and cement exhibit satisfying performance over their counterparts. Nevertheless, significant concerns are associated with those chemicals, such as sulfate, carbonation attack, and its environmental impact. The efficiency of the polyurethane (PU) foam as a stabilizing agent for the pavement subbase layer and foundation systems concerned with relative movement and excessive settlement problems has been confirmed in many experimental and in-situ studies. However, only a few studies preliminary explored the effect of this injected stabilizer on the response of swelling soil. This review highlights several beneficial mechanical and physical characteristics of the Hydrophobic PU foam, which may nominate this material to be viable alternative stabilizers for the problematic expansive soil. The paper also identified future research needs to fulfill the scientific and practical gap in using PU foam for expansive soil treatment.